2013
DOI: 10.1155/2013/340508
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Multiple Sclerosis: An Up-to-Date Overview

Abstract: During the last decades, the effort of establishing satisfactory biomarkers for multiple sclerosis has been proven to be very difficult, due to the clinical and pathophysiological complexities of the disease. Recent knowledge acquired in the domains of genomics-immunogenetics and neuroimmunology, as well as the evolution in neuroimaging, has provided a whole new list of biomarkers. This variety, though, leads inevitably to confusion in the effort of decision making concerning strategic and individualized thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 163 publications
2
72
0
3
Order By: Relevance
“…Both environmental and genetic factors have been implicated in the pathogenesis of the disease leading to the well-known consideration of MS as a complex multi-factorial disease entity [1]. Concerning genetics, linkage studies in many populations consistently have showed that the human leukocyte antigens (HLA), products of the Major Histocompatibility Complex (MHC) on chromosome 6p21.3 are linked to MS [1,2]. MHC represents a cluster of highly polymorphic genes, including the HLA-Class I, II and III genes that encode proteins which serve antigen presentation to T-lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Both environmental and genetic factors have been implicated in the pathogenesis of the disease leading to the well-known consideration of MS as a complex multi-factorial disease entity [1]. Concerning genetics, linkage studies in many populations consistently have showed that the human leukocyte antigens (HLA), products of the Major Histocompatibility Complex (MHC) on chromosome 6p21.3 are linked to MS [1,2]. MHC represents a cluster of highly polymorphic genes, including the HLA-Class I, II and III genes that encode proteins which serve antigen presentation to T-lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines have various functions in health and diseases, especially in MS (13)(14)(15)(16). One of the most important cytokines that directly contributes to the immunopathogenesis of MS is IL-33 (17), a recently discovered cytokine, taking part in various inflammatory and autoimmune diseases like psoriasis, lupus erythematous, ulcerative colitis and MS (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The determination of biomarkers of inflammation and neurodegeneration in body fluids, combined with the use of non-conventional MRI with the ability to detect changes in the normal appearing brain tissue, could assist in the detection of a sequence of cellular and molecular events, inside and out of the CNS, that occur before fulfilling the current definition of NEDA composite. Multiple biomarkers have been identified in MS, but their validation and clinical application have not been established 7, 8 . Teunissen recently discussed the use of biomarkers for MS such as N-acetylaspartate (representing mitochondrial dysfunction and/or neuro-axonal loss), chitinase 3 like-protein 1 (meaning reactive astrogliosis and microglial activity), neurofilament light chain (related to axonal loss) and glial fibrillary acidic protein (representing astrocytic cytoskeleton injury).…”
Section: Background Activity Beyond the Surveillance Of Nedamentioning
confidence: 99%